2019
DOI: 10.1111/ejss.12748
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale observation on the effects of burrowing activities of ants on soil hydraulic processes

Abstract: Summary Ants alter soil structure when making their nests and the fresh soil aggregates brought to the surface become available for erosion. However, the effects of burrowing activities of ants on soil hydrological processes are unclear. In this study, the effects of Tetramorium caespitum, Messor aciculatus and Camponotus japonicus nests on the preferential flow and soil surface hydrologic processes at a small scale were assessed on the Loess Plateau. Soil dyeing and rainfall simulation experiments were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Previous studies estimated both positive as well as negative impacts of burrowing animals on sediment redistribution rates. The results were obtained by applying tests under laboratory conditions using rainfall simulators, conducting several field campaigns weeks to months apart, or by measuring the volume of excavated or eroded sediment in the field using methods such as erosion pins, splash boards, or simple rulers (Imeson and Kwaad, 1976;Reichman and Seabloom, 2002;Wei et al, 2007;Le Hir et al, 2007;Li et al, 2018;Li et al, 2019c;Li et al, 2019b;Voiculescu et al, 2019;Chen et al, 2021;Übernickel et al, 2021b;Li et al, 2019a). Although burrowing animals are generally seen as ecosystem engineers (Gabet et al, 2003;Wilkinson et al, 2009), their role in soil erosion, in general, and for numerical soil erosion models, in particular, is, to date, limited to predictions of the burrow locations and particle mixing at these locations (Black and Montgomery, 1991;Meysman et al, 2003;Yoo et al, 2005;Schiffers et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies estimated both positive as well as negative impacts of burrowing animals on sediment redistribution rates. The results were obtained by applying tests under laboratory conditions using rainfall simulators, conducting several field campaigns weeks to months apart, or by measuring the volume of excavated or eroded sediment in the field using methods such as erosion pins, splash boards, or simple rulers (Imeson and Kwaad, 1976;Reichman and Seabloom, 2002;Wei et al, 2007;Le Hir et al, 2007;Li et al, 2018;Li et al, 2019c;Li et al, 2019b;Voiculescu et al, 2019;Chen et al, 2021;Übernickel et al, 2021b;Li et al, 2019a). Although burrowing animals are generally seen as ecosystem engineers (Gabet et al, 2003;Wilkinson et al, 2009), their role in soil erosion, in general, and for numerical soil erosion models, in particular, is, to date, limited to predictions of the burrow locations and particle mixing at these locations (Black and Montgomery, 1991;Meysman et al, 2003;Yoo et al, 2005;Schiffers et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all earthworms (mean weight of 4.4 AE 0.8 g) drilled into the soil within half an hour, and left at least 150 burrows with entrances of approximately 5 mm in diameter on the soil surface (Figure 5c). Li et al (2019b) studied the effects of ant burrows on soil hydrological processes and found that nests of Messor aciculatus (nest entrance diameter of 0.33 cm)…”
Section: Effects Of Earthworm Activities On Water Infiltration and So...mentioning
confidence: 99%
“…Experimental study of the effects of termites and ants on soil infiltration rates has been investigated by many authors in a wide variety of environmental and topographic settings (e.g. Elkins et al ., 1986; Eldridge, 1993, 1994; Mando et al ., 1996; Wang et al ., 1996; Cammeraat et al ., 2002; Leonard et al ., 2004; James et al ., 2008; Cheik et al ., 2018; Li et al ., 2019b). Most of these studies have demonstrated that soil infiltration rates and porosity were significantly higher on termite‐ or ant‐modified soils than on non‐nest soils.…”
Section: Indirect Geomorphic Effects Of Insectsmentioning
confidence: 99%